Estudio del proceso de la elaboración de vinagre a partir de desechos de frutas - Chávez Lema, Jonathan Gabriel (2019)
Through the document analysis method, a study of the methods used for the production of vinegar according to the conditions of the Helados Salcedo factory was carried out, which facilitates the raw material for its preparation in order to take advantage of the amount of waste produced and give it added value. It was justified that the Luxembourgish Method is the most suitable for the production of vinegar because it is an artisanal method according to the production of ice cream that corresponds to the main production of the company, and offers the possibility of controlling the parameters of the process of manufacturing. The objective of the work is "Propose a method for obtaining vinegar on an industrial scale that allows the reuse of fruit wastes resulting from the production of ice cream." The factory processes used for ice cream were characterized with the consequent calculation of volumes and masses of their procedures to determine the amount of raw material, as well as a positive aspect to highlight, the raw material has no acquisition cost and this decreases Production costs In the second stage, the above-mentioned method for vinegar production was selected. In the third phase of the investigation, the procedures and parameters of the method detailed above were proposed and the economic study was carried out for the implementation of the selected method and it results in the investment being recovered in a period of 3 years, 10 months and 21 days. , also detailing the production and marketing costs of the vinegar that is intended to be produced.